The role of MyD88 in embryonal carcinoma stem cells - Sulaiman, Gomaa M. A. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2015)
Tumour-initiating cells are known to share some properties with stem cells. These so called 'Cancer Stem Cells' (CSCs) are highly tumourigenic in the undifferentiated state, a property that is lost upon CSC differentiation. For many years, our group has studied CSC differentiation in a nullipotent embryonal carcinoma CSC cell line (2102Ep), which can resist differentiation to produce highly-aggressive tumours. Previous work in the lab highlighted a potential role for Toll-Like Receptor (TLR) Signaling mediator protein Myeloid Differentiation Response Gene 88 (MyD88) in the mechanism through which 2102Ep cells resist differentiation.
Keywords: Histopathology & Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin.